REINTERPRETASI NASIKH DAN MANSUKH DALAM AL-QUR’AN: Analisis Ayat Khamr Perspektif Kerangka Filsafat Maqasid Al-Syariah Jasser Auda - Dalailul Choir (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
The debate surrounding the concept of nāsikh and mansūkh in the Qur’an, particularly in verses concerning khamr (intoxicants), remains a significant issue in Qur’anic exegesis and the sources of Islamic law (uṣūl al-fiqh). Classical interpretations that understand legal replacement as a gradual abrogation are often considered insufficient in addressing contemporary methodological needs, especially within increasingly complex contexts. This study aims to reinterpret the khamr verses, which have traditionally been viewed through the framework of nāsikh–mansūkh, by employing the maqāṣid al-sharī‘ah philosophical framework proposed by Jasser Auda. The research adopts a qualitative method based on library research, utilizing relevant literature that supports the analysis. The findings indicate that the gradual revelation of the khamr verses should not necessarily be understood as chronological legal abrogation, but rather as a value-based process that emphasizes the objectives of the Sharī‘ah, particularly the preservation of human intellect and life. This study concludes that classical maqāṣid concepts should not remain static; instead, they must evolve in response to contextual demands. Jasser Auda argues that traditional maqāṣid should be expanded beyond the scope of individual welfare toward a broader framework of universal public good.